Non-nucleophilic Grignard Synthesis of Bridged Pyridine–Oxazoline Ligands and Evaluation in Palladium-Catalysed Allylic Alkylation - Sutton, Grace; O’Leary, Patrick (Synlett, 2023)
The synthesis of eight pyridine-oxazoline ligands, five of which have never been reported previously, is described. The ligands were prepared in two efficient steps, initially preparing 2-pyridyl alkylnitriles, followed by their conversion into oxazolines ligands using chiral amino alcohols and zinc chloride. The 2-pyridyl nitriles are prepared via a novel SNAr alkylation reaction of 2-bromopyridine with alkyl nitriles using methylmagnesium chloride as a non-nucleophilic base in conjunction with an amine mediator. This methodology allows preparation of the existing gem-dimethyl motif and its elaboration beyond previously prepared ligands in fewer steps with simplicity and scalability. The toleration of variation in the nitrile, halopyridine, and amino alcohol starting materials allows for other novel bridging substitution which gives new ligands with enhanced reactivity. The library of bridging ligands was applied to the Pd-catalysed allylic alkylation of 1,3-diphenylprop-2-enyl acetate with dimethyl malonate and afforded conversions of up to 100% and enantioselectivities of up to 68%.
Keywords: nitriles; SNAr alkylation; Grignard reaction; pyridine oxazoline; zinc chloride